Effect of media and gelling agents on shoot organogenesis of Liriope platyphylla - Kim, Young Chang; Park, Woo Tae; Sathasivam, Ramaraj; Kim, Haeng-Hoon; Kim, Jae Kwang; Park, Sang Un (Journal of Phytology, 2023)
Liriope platyphylla can be multiplied either by planting seeds or dividing its tuberous roots. In this study, a method for L. platyphylla plant shoot organogenesis from meristem explants was developed employing medium and gelling agents. For the selection of optimal medium conditions for shoot organogenesis, the effects of full- and half-strength B5, SH, and MS media were examined. Different concentrations of the gelling agents such as phytagar (6, 7, 8, and 9 g L-1) and gellan gum (2, 3, 4, and 5 g L-1) were examined for efficient shoot formation. The results revealed the superiority of half-strength MS basal medium in shoot organogenesis and growth of Liriope platyphylla. But the half-strength B5 media performed poorly. Compared to plant agar, gellan gum performed well in terms of shoot regeneration and shoot length. When gellan gum was used at 3 g L-1 the maximum number of shoots explant-1 (5.8) and longest shoot (45.8 mm) was observed but the lowest number of shoots explant-1 (3.2) and shortest shoot (21.4 mm) was registered with 5 g L-1. It is proposed from our study that half-strength MS media and gellan gun gelling agent at 3 g/l could be applied in shoot organogenesis and growth of L. platyphylla.